Methods for Estimating Item-Score Reliability. Issue 7 (October 2018) - Zijlmans, Eva A. O.; van der Ark, L. Andries; Tijmstra, Jesper; Sijtsma, Klaas
Reliability is usually estimated for a test score, but it can also be estimated for item scores. Item-score reliability can be useful to assess the item's contribution to the test score's reliability, for identifying unreliable scores in aberrant item-score patterns in person-fit analysis, and for selecting the most reliable item from a test to use as a single-item measure. Four methods were discussed for estimating item-score reliability: the Molenaar–Sijtsma method (method MS), Guttman's methodλ 6, the latent class reliability coefficient (method LCRC), and the correction for attenuation (method CA). A simulation study was used to compare the methods with respect to median bias, variability (interquartile range [IQR]), and percentage of outliers. The simulation study consisted of six conditions: standard, polytomous items, unequalα parameters, two-dimensional data, long test, and small sample size. Methods MS and CA were the most accurate. Method LCRC showed almost unbiased results, but large variability. Methodλ 6 consistently underestimated item-score reliabilty, but showed a smaller IQR than the other methods.